1998
DOI: 10.3892/ijmm_00000091
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PPARγ is reduced by medium supplementation with L-glutamine in human colorectal Caco-2 cells

Abstract: Abstract. Peroxisome proliferator-activated receptor-γ (PPARγ) belongs to the nuclear hormone receptor family. This receptor is implicated in colon cell differentiation and in colon cancer. Receptor activation by specific agonists has been shown to protect against colon cancer progression. PPARγ protein content within cells is modulated by several mechanisms, including proteasome degradation, activation of Wnt signalling pathways and presence of fermentation products such as butyrate. Herein, we investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(29 reference statements)
1
1
0
Order By: Relevance
“…These studies indicate that glutamine has different regulatory effects on PPARγ levels in different intestinal cell types. In our study, the expression levels of PPAR-γ decreased significantly after the fish were fed different concentrations of Gln, which was in line with the results of the previous study on human colorectal Caco-2 cells (Fiatte et al, 2008). The molecular mechanism of the inhibitory effect of Gln on PPAR-γ expression in fish needs further study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These studies indicate that glutamine has different regulatory effects on PPARγ levels in different intestinal cell types. In our study, the expression levels of PPAR-γ decreased significantly after the fish were fed different concentrations of Gln, which was in line with the results of the previous study on human colorectal Caco-2 cells (Fiatte et al, 2008). The molecular mechanism of the inhibitory effect of Gln on PPAR-γ expression in fish needs further study.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have shown that glutamine can enhance the transcriptional activity of PPAR-γ in a dose-and time-dependent manner in the intestinal epithelial cell line IEC-6 by stimulating the PPAR-γ ligands 15-HETE and 13-OXO-ODE (Ban, Sprunt, Martin, Yang, & Kozar, 2011). However, in human colorectal Caco-2 cells, Fiatte et al, (2008) reported that PPAR-γ expression levels were decreased by medium supplementation with l-glutamine. These studies indicate that glutamine has different regulatory effects on PPARγ levels in different intestinal cell types.…”
Section: Discussionmentioning
confidence: 99%